2020
DOI: 10.3390/fishes5030027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Environmental DNA to Detect Grass Carp Spawning Events

Abstract: The timing and location of spawning events are important data for managers seeking to control invasive grass carp populations. Ichthyoplankton tows for grass carp eggs and larvae can be used to detect spawning events; however, these samples can be highly debris-laden, and are expensive and laborious to process. An alternative method, environmental DNA (eDNA) technology, has proven effective in determining the presence of aquatic species. The objectives of this project were to assess the use of eDNA collections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This peak matches the reproduction period of most of the lacustrine species detected, suggesting that species phenology plays a major role in the temporal variability of eDNA signal. eDNA concentration followed a strong seasonal variation, with a peak of eDNA concentration or number of reads observed during fish reproduction [88,89]. This was also observed with metabarcoding data for late autumn/winter spawners, such as Coregonus lavaretus.…”
Section: Plos Onesupporting
confidence: 73%
“…This peak matches the reproduction period of most of the lacustrine species detected, suggesting that species phenology plays a major role in the temporal variability of eDNA signal. eDNA concentration followed a strong seasonal variation, with a peak of eDNA concentration or number of reads observed during fish reproduction [88,89]. This was also observed with metabarcoding data for late autumn/winter spawners, such as Coregonus lavaretus.…”
Section: Plos Onesupporting
confidence: 73%
“…There are several studies using eDNA that focused on fish spawning (e.g., Erickson et al, 2016;Bylemans et al, 2017;Tillotson et al, 2018;Thalinger et al, 2019;Hayer et al, 2020;Yatsuyanagi et al, 2020). Thalinger et al (2019) and Yatsuyanagi et al (2020) showed that eDNA concentrations increased because of fish migration into rivers during the spawning season.…”
Section: Introductionmentioning
confidence: 99%
“…Thalinger et al (2019) and Yatsuyanagi et al (2020) showed that eDNA concentrations increased because of fish migration into rivers during the spawning season. Erickson et al (2016); Tillotson et al (2018), andHayer et al (2020) reported that fish spawning behavior in rivers could temporarily increase eDNA concentrations and the spawning behavior could be captured using eDNA. These studies show that eDNA may increase with fish spawning behavior, perhaps because DNA fragments from sperm and dead fish promote a temporary increase in the eDNA concentrations (Bylemans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reviews of this rapidly developing topic [9]. In this volume, Hayer and colleagues [10] describe how eDNA presence in river waters shows a positive relationship to the presence of invasive grass carp, Ctenopharyngodon idella, in North America, especially when these fish are spawning. Because, grass carp, like many invasive fishes, are very difficult to sample, this is an important observation, especially if eDNA concentration could be directly linked to reproductive state.…”
Section: Techniques To Assess the Presence And Distribution Of Invasi...mentioning
confidence: 99%